Advancing aluminum-ion batteries: unraveling the charge storage mechanisms of cobalt sulfide cathodes - Andrew Grindal; Gisele Azimi (Scientific Reports)
Abstract Rechargeable aluminum-ion batteries (AIBs) stand out as a potential cornerstone for future battery technology, thanks to the widespread availability, affordability, and high charge capacity of aluminum. However, the efficacy of current AIBs on the market is significantly limited by the charge storage process within their graphite cathodes. To fully realize the capabilities of AIBs, the discovery of a new cathode material is essential. Transition metal sulfides present an attractive option for cathode materials, although there has been a variety of conflicting reports regarding the exact nature of their charge storage mechanisms. This paper investigates cobalt sulfide (CoSx) cathodes in AIBs, with a particular focus on deciphering the mechanisms of charge storage. Through synthesis, electrochemical testing, and post-cycling characterization, we illuminate the roles of AlCl4 − intercalation, cobalt sulfide to Al2S3 conversion, and sulfur to Al2S3 conversion in charge storage. As cycling progresses, Al2S3 synthesis from segregated sulfur segments emerged as the predominant mechanism, showcasing its potential to fully leverage the high capacity of aluminum metal and propel AIBs towards higher energy densities. Despite these promising findings, the study also uncovered significant challenges, notably material loss, intra-cathode diffusion limitations, and irreversible reactions that precipitously diminish charge capacity over time. These issues highlight the critical need for enhanced electrode stability, improved electrolyte compatibility, and accelerated aluminum diffusion. The research paves the way for further exploration of transition metal sulfides as cathode materials in AIBs, highlighting the imperative for innovations that bolster mechanical and chemical stability while optimizing ion transport. This work not only contributes to the fundamental understanding of charge storage in AIBs but also charts a course for the development of more durable and efficient battery systems.